Use of Traditional Medicine in the Treatment of Skin Diseases - Suyunqulova Shahrizoda Shavkatjon qizi; Bahodirova Elshoda Mahammadali qizi (American Journal of Biomedicine and Pharmacy, 2025)
Medicinal plants have been widely used since ancient times and continue to serve as important therapeutic resources in traditional and modern healthcare. This article examines the biological and dermatological significance of Matricaria chamomilla, Aloe vera, and Calendula officinalis—three medicinal species rich in bioactive compounds that contribute to their long-standing use in treating skin conditions. The phytochemical constituents of these plants, including flavonoids, terpenoids, carotenoids, polysaccharides, essential oils, and organic acids, exhibit a broad spectrum of pharmacological activities such as anti-inflammatory, antioxidant, antimicrobial, wound-healing, and immunomodulatory effects. German chamomile demonstrates therapeutic potential in reducing inflammatory mediators, enhancing skin barrier repair, and supporting wound healing, while Aloe vera exhibits profound regenerative, anti-inflammatory, and collagen-stimulating properties through compounds such as acemannan, aloin, and glucomannan. Calendula officinalis, rich in flavonoids, triterpenoids, and carotenoids, offers notable antioxidant, antiseptic, and anti-inflammatory benefits that accelerate wound closure and alleviate dermatitis, burns, and irritations. Given the rising global interest in natural therapies and the increasing prevalence of dermatological disorders, these plants represent valuable resources for developing safe, effective, and accessible treatments. This article highlights their chemical profiles, mechanisms of action, and therapeutic potential in managing various skin diseases.